1995
DOI: 10.1042/cs0880173
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effects of Continuous Positive Airway Pressure in Humans with Normal and Impaired Left Ventricular Function

Abstract: 1. Continuous positive airway pressure increases intrathoracic pressure, thereby decreasing left ventricular preload and afterload. We hypothesized that there would be a dose-related alteration in cardiac and stroke volume indices in response to continuous positive airway pressure in normal subjects and patients with congestive heart failure and that the direction of response among those with heart failure would be related to left ventricular preload. 2. Cardiac and stroke volume indices were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 0 publications
1
46
1
Order By: Relevance
“…16 Because the failing heart is very sensitive to changes in afterload, such an effect could also boost SV and CO by recruiting the respiratory system to assist left ventricular ejection in the face of deteriorating cardiac function. 17,18 This mechanism might be comparable to that from chest compressions during cardio-pulmonary resuscitation for cardiac arrest, 19,20 and to voluntary coughing during conscious cardiac arrest in the cardiac catheterization laboratory where generation of positive P IT augments SV and CO. 21 By this means, in patients with HFrEF and very compromised cardiac function, the respiratory system may be recruited to assist cardiac pumping activity via active expiration and generation of positive P IT during the hyperpnea phase of CSR-CSA.…”
Section: Discussionmentioning
confidence: 99%
“…16 Because the failing heart is very sensitive to changes in afterload, such an effect could also boost SV and CO by recruiting the respiratory system to assist left ventricular ejection in the face of deteriorating cardiac function. 17,18 This mechanism might be comparable to that from chest compressions during cardio-pulmonary resuscitation for cardiac arrest, 19,20 and to voluntary coughing during conscious cardiac arrest in the cardiac catheterization laboratory where generation of positive P IT augments SV and CO. 21 By this means, in patients with HFrEF and very compromised cardiac function, the respiratory system may be recruited to assist cardiac pumping activity via active expiration and generation of positive P IT during the hyperpnea phase of CSR-CSA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in subjects with normal heart function, acute application of CPAP is known to decrease left ventricular preload more than left ventricular afterload, leading to a reduction in cardiac output. 9 However, our OSAS subjects did not show any change in SBP or DBP during sleep relative to wakefulness when only minimal CPAP was applied. The CPAP-induced increase in lung volume itself may have also contributed to some increase in vagal activity and reduction in sympathetic drive.…”
Section: Potential Confounding Effects Of Cpapmentioning
confidence: 95%
“…Bradley et al [12] demonstrated a significant increase in both cardiac index and stroke volume after 10 min of nasal CPAP at 5 cm H 2 O in those patients with a pulmonary capillary wedge pressure [12 mmHg. The presence of an elevated filling pressure appears to be important in regards to the cardiac response to CPAP therapy [55]. Improvements in LVEF have been noted with CPAP therapy when used from 1 to 3 months [11,[13][14][15][16][17][18].…”
Section: Oxygen Therapymentioning
confidence: 97%